Pengaruh Aglomerasi, Kualitas Sumber Daya Manusia (SDM), Ketimpangan Pendidikan, dan Pertumbuhan Ekonomi Terhadap Ketimpangan Pendapatan di Indonesia - Hanifah Muslimah; Dewi Zaini Putri (Universitas Negeri Padang, 2021)
This study aims to analyze the effect of agglomeration, the quality of human resources (HR), educational inequality and economic growth on income inequality in Indonesia. The type of data used in this study uses panel data (cross section and time series data from 34 provinces in Indonesia from 2011-2018). While the analytical method used in this study uses Panel Regression analysis using a fixed effect model and the results in this study indicate that agglomeration has a positive and significant effect on income inequality in Indonesia, the quality of human resources (HR) has a negative and significant effect. on income inequality in Indonesia, education inequality has a positive and significant effect on income inequality and economic growth has a positive and insignificant1 effect on income inequality in Indonesia.